Parental factors and their effects on students' learning in Mathematics (Siddhajyoti Interdisciplinary Journal, 2020)
Children's academic achievement and educational attainment have been studied within different frameworks. This study has focused on parents’ education, occupation, and economic status. The objective of this study was to measure effect of parental qualification, occupation, and economic status and mathematical achievement of children in Sindhuli District, Nepal. The design of the study was survey and method of study was quantitative.The population of this research was of 9th grade students of Sindhuli District. The sample consists of 90 students of 9th grade in Kamalamai Municipality, Sindhuli. Both primary and secondary data was used to draw the conclusion of this research. Questionnaire was tool for primary data collection and school records were used as secondary data of this study. To test the significance Chi-square statistical tool was used at 5% level of significance. Conclusion based on the finding of this study was that there is significance relationship between parental qualification, profession, economic status and mathematical achievement of their children. This study will be one of the reference materials in the field for learners and its stakeholders. Specifically the teacher can use the result of this study during teaching in the classroom.